Statistical analysis of high frequency ultrasonic backscattered signals from basal cell carcinomas. - Petrella LI; de Azevedo Valle H; Issa PR; Martins CJ; Machado JC; Pereira WC; Petrella, Lorena Itatí; de Azevedo Valle, Heliomar; Issa, Paulo Roberto; Martins, Carlos José; Machado, João Carlos; Pereira, Wagner Coelho A (Ultrasound in Medicine & Biology, 2012)
A statistical approach was implemented in the study of histologic characteristics from ex vivo basal cell carcinomas, based on the properties of backscattered acoustic waves, for the purpose of evaluating the method as a diagnostic tool. The study was developed using an ultrasound biomicroscope working at a frequency of 45 MHz. The parameters examined were signal-to-noise ratio (SNR), and shape parameters from the Weibull (b(W)) and generalized gamma (c(GG) and υ(GG)) probability density functions. Twenty-seven carcinomatous skin samples were obtained from volunteer patients and classified into two groups (BCC1 and BCC2) based on the distribution patterns of their tumor nests; also, seven non-tumoral samples were used for comparative purposes. Significant differences between groups were obtained for all studied parameters. The successful differentiation between some tissue groups suggests its potential use for carcinoma characterization.